Remote Switching of Elastic Movement of Decorated Ligand Nanostructures Controls the Adhesion‐Regulated Polarization of Host Macrophages. (17th February 2021) - Thangam, Ramar; Kim, Myeong Soo; Bae, Gunhyu; Kim, Yuri; Kang, Nayeon; Lee, Sungkyu; Jung, Hee Joon; Jang, Jinhyeok; Choi, Hyojun; Li, Na; Kim, Minjin; Park, Sangwoo; et al.
Abstract: Design of materials with remote switchability of the movement of decorated nanostructures presenting cell‐adhesive Arg‐Gly‐Asp ligand can decipher dynamic cell‐material interactions in decorated ligand nanostructures. In this study, the decoration of ligand‐bearing gold nanoparticles (ligand‐AuNPs) on the magnetic nanoparticle (MNP) with varying ligand‐AuNP densities is demonstrated, which are flexibly coupled to substrate in various MNP densities to maintain constant macroscopic ligand density. Magnetic switching of upward ("Upper Mag") or downward ("Lower Mag") movement of varying ligand‐AuNPs is shown via stretching and compression of the elastic linker, respectively. High ligand‐AuNP densities promote macrophage adhesion‐regulated M2 polarization that inhibits M1 polarization. Remote switching of downward movement ("Lower Mag") of ligand‐AuNPs facilitates macrophage adhesion‐regulated M2 polarization, which is conversely suppressed by their upward movement ("Upper Mag"), both in vitro and in vivo. These findings are consistent with human primary macrophages. These results provide fundamental understanding into designing materials with decorated nanostructures in both high ligand‐AuNP density and downward movement of the ligand‐AuNPs toward the substrate to stimulate adhesion‐regulated M2 polarization of macrophages while suppressing pro‐inflammatory M1 polarization, thereby facilitating tissue‐healing responses. Abstract : The decoration of ligand‐bearing gold nanoparticles on the magnetic nanoparticle that are flexibly coupled to a substrate without varying macroscopic ligand density is demonstrated. It is shown that magnetic switching of elastic movement of varying ligand‐bearing gold nanoparticle densities regulates the adhesion‐mediated polarization of macrophages, both in vitro and in vivo.